Steam inquiry learning model with cartoon film media on indonesian language learning outcomes for fifth-grade students - Taufiqurrohmah Taufiqurrohmah; Rusnilawati Rusnilawati; Zingiswa Mybert Monica Jojo (Jurnal Ilmiah Pendidikan Dasar, 2025)
This study assessed the effectiveness of incorporating the STEAM-Inquiry Learning model, supplemented with cartoon film media, on the learning outcomes of fifth-grade students in the Indonesian Language class. The lack of innovative learning media has resulted in low student engagement in Indonesian language lessons. This research employed a quantitative approach with a quasi-experimental design. The STEAM-Inquiry Learning model was implemented over three learning periods, utilizing cartoon film media to enhance student engagement and academic performance. Two groups of students were compared: an experimental group (N=14) receiving the STEAM-Inquiry Learning model with cartoon film media, and a control group (N=18) utilizing the contextual learning model. Data were collected through validated learning outcome tests and reliable instruments. Data analysis revealed significant differences in learning outcomes between the two groups. Students exposed to the STEAM-Inquiry Learning model with cartoon film media demonstrated significantly improved Indonesian Language learning outcomes. These findings highlight the importance of integrating innovative learning models to enhance the effectiveness of Indonesian language education, particularly in improving students’ literacy skills.